MODIFICATION OF CHITOSAN BY GRAFT COPOLYMERIZATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
The interaction of N-monomethylol urea with maleic anhydride is studied. The product of this reaction forms an oligomeric monomer by condensation with chitosan. This oligomeric monomer has a capacity of copolymerization in aqueous media with other soluble monomers such as acrylic acid forming crosslinked water-swelling copolymer. The products obtained in mentioned above reactions were investigated by IR-spectroscopy and elemental analysis.
Keywords: chitosan; maleic anhydride; N-methylol urea; crosslinked water-swelling copolymer